A Study on Advertisement on Consumer Behavior towards Digital Marketing and Its Impact on Buying Behavior: Exploring the Impact of Digital Marketing on Youth's Buying Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the customer-orientated retail climate the consumer's shopping behavior is shifting more rapidly. In terms of commodity, price, functionality, cost, packaging, acquisition behavior, rank, generation, the market behavior varies the customer's size, etc., youth is the more difficult category to balance. The shifting tastes of today's young people influence the purchase trend and much of the time varies according to the patterns of mode and taste. Digital marketing has already provided the retail marketer with a range of obstacles. The young generation is obsessed with internet purchasing rather than traditional sales. Focused on the pressures of the millennial generation, the advertisers have to adopt the creative form of marketing. The attitudes and conduct habits of young people are more prominent in purchasing behavior. Internet media and its implications for young people's buying behaviors, as the key challenge, are.